Access to Fluorinated Quaternary Stereogenic Centers via Palladium-Catalyzed Asymmetric Allylic C–H Alkylation - Wei, Jia-Hui; Jin, You-Xiang; Wang, Pu-Sheng; Gong, Liu-Zhu (Synlett, 2023)
A Pd-catalyzed branch- and enantioselective allylic C–H alkylation reaction has been developed for the rapid assembly of fluorinated quaternary stereogenic centers from allylarenes and prochiral α-fluorinated esters. Using chiral phosphoramidite as ligand and 2,5-diphenylquinone as oxidant, the reaction proceeds smoothly under mild conditions and tolerates a broad scope of substrates, resulting in α-quaternary fluorinated ester products with high levels of yields, enantioselectivities, and regioselectivities.
Keywords: palladium catalysis; allylic C–H alkylation; phosphoramidite; quaternary stereogenic center; fluorinated carbon